Energy metrics and tradeoff of nonlinear multi-agent consensus subject to DoS attacks - Zhao, Lingzhi; Lu, Jianquan; Ruan, Qihua; Huang, Tingwen (Information sciences, 2025)
This paper investigates the problem of fixed-time leader-following consensus in nonlinear multi-agent systems (NMASs) subject to malicious DoS (Denial-of-Service) attacks. From the perspectives of time cost (TC) and energy cost (EC), as well as the random impact of attacks on information interaction, we propose an innovative switching control approach that combines the strengths of both finite-time and fixed-time control strategies. We derive sufficient and verifiable mathematical criteria for achieving leader-following consensus. Specifically, we demonstrate, both theoretically and numerically, that there is a tradeoff between TC and EC: the coexistence of the control parameters k and α implies that reducing TC inevitably increases EC. Finally, we highlight that different optimal values of the steepness exponent and control gain should be selected depending on the weighting metrics used, to minimize the total cost of time and energy.